Willingness to pay for conserving Layawan Watershed for domestic water supply in Oroquieta City, Philippines - Manlosa, Aisa O.; Briones, Nicomedes D.; Alcantara, Antonio J.; Florece, Leonardo M. (2013)
The sustainability of domestic water supply from the Layawan Watershed in Oroquieta City critically depends on past and present conservation activities and the availability of funds from stakeholders such as households, communities, non-government organizations, private entities and government agencies. This study determined the willingness to pay (WTP) particularly of households in Oroquieta City to finance conservation projects in Layawan Watershed to ensure the sustainability of domestic water supply. A household survey of randomly selected 278 respondents was conducted using the dichotomous choice referedum format.

The Heckman's two-stage analysis for the parametric estimation of mean WTP yielded the values of PhP 4.00, PhP 6.00 and PhP 7.00 per month for mandatory, voluntary and pooled data sets, respectively.

The households are willing to contribute funds for conserving Layawan Watershed as supported by the total WTP of Oroquieta City's population that ranges from PhP 117,845.00 (from lower bound estimate of PhP 2.00) to PhP 471,380.00 (from upper bound estimate of PhP 8.00) in five years, discounted at 6%.